Conversational correlates of rapid social judgments of children and adolescents with and without ASD. (1st February 2021) - Shield, Aaron; Wang, Xin; Bone, Daniel; Narayanan, Shrikanth; Grossman, Ruth B
ABSTRACT: Autism spectrum disorder (ASD) is characterized by deficits in social communication, and even children with ASD with preserved language are often perceived as socially awkward. We ask if linguistic patterns are associated with social perceptions of speakers. Twenty-one adolescents with ASD participated in conversations with an adult; each conversation was then rated for the social dimensions of likability, outgoingness, social skilfulness, responsiveness, and fluency. Conversations were analysed for responses to questions, pauses, and acoustic variables. Wide intonation ranges and more pauses within children's own conversational turn were predictors of more positive social ratings while failure to respond to one's conversational partner, faster syllable rate, and smaller quantity of speech were negative predictors of social perceptions.